2005
DOI: 10.1186/bcr983
|View full text |Cite|
|
Sign up to set email alerts
|

Claudin-1, -3 and -4 proteins and mRNA expression in benign and malignant breast lesions: a research study

Abstract: Introduction We compared levels of protein and mRNA expression of three members of the claudin (CLDN) family in malignant breast tumours and benign lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(120 citation statements)
references
References 32 publications
4
112
1
3
Order By: Relevance
“…Compared to human mammary tissue, the same CLDNs are present in canine mammary epithelial cells (Tőkés et al, 2005). This study provided further evidence that CLDN proteins are ancient, conservative molecules that are preserved throughout different species.…”
Section: Acta Veterinaria Hungarica 56 2008supporting
confidence: 51%
“…Compared to human mammary tissue, the same CLDNs are present in canine mammary epithelial cells (Tőkés et al, 2005). This study provided further evidence that CLDN proteins are ancient, conservative molecules that are preserved throughout different species.…”
Section: Acta Veterinaria Hungarica 56 2008supporting
confidence: 51%
“…CLAUDIN-1 expression is altered in several human malignancies (Resnick et al 2005, Tokes et al 2005, Chao et al 2009) and subcellular expression of CLAUDIN-1 has been linked with tumour invasiveness and an advanced tumour stage (Dhawan et al 2005, Kinugasa et al 2012, Eftang et al 2013. We asked whether CLAUDIN-1 is relevant for the biological behaviour of human follicular thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor progression, tight junction assembly is often disrupted resulting in the loss of cell membrane localized tight junction proteins (Resnick et al 2005, Tokes et al 2005. For CLAUDIN-1, an altered protein expression as well as subcellular localization has been observed in common human malignancies including colon, lung and breast cancer and melanoma (Tokes et al 2005, Chao et al 2009, Nemeth et al 2010. Furthermore, subcellular CLAUDIN-1 expression has been associated with a more aggressive tumour behaviour (Miwa et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified the expression of claudins in several cancer types, including breast, pancreatic, liver and esophageal cancer (10,(29)(30)(31)(32)(33). Claudin-1 expression was reported be attenuated in breast cancer as well as colon cancer (31,34,35). In addition, the expression levels of claudin-1, claudin-3, claudin-4 and claudin-5 were all significantly decreased in diffuse adenocarcinoma and were essential for determining the phenotype and loose cohesion of cells in diffuse gastric carcinoma (15).…”
Section: Claudin-1 Claudin-4 ----------------------------------------mentioning
confidence: 95%